2002
DOI: 10.1200/jco.2002.20.4.957
|View full text |Cite
|
Sign up to set email alerts
|

Successful Adenovirus-Mediated Wild-Type p53 Gene Transfer in Patients With Bladder Cancer by Intravesical Vector Instillation

Abstract: Intravesical instillation of SCH 58500 combined with a transduction-enhancing agent is safe, feasible, and biologically active in patients with bladder cancer. Studies to evaluate the clinical efficacy of this treatment in patients with localized high-risk bladder cancer are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Vaccination against mutant P53 has been shown to be effective in tumor-bearing mice [150,151]. Several peptide vaccines and dendritic cell vaccines utilizing mutant P53-targeted immunotherapy are in clinical development [152][153][154][155]. A number of Phase I/II immunization trials have been conducted so far using P53 immunogens, but unfortunately none of them have shown acceptable clinical efficacy [156].…”
Section: Targeting Tp53 In Drug Developmentmentioning
confidence: 99%
“…Vaccination against mutant P53 has been shown to be effective in tumor-bearing mice [150,151]. Several peptide vaccines and dendritic cell vaccines utilizing mutant P53-targeted immunotherapy are in clinical development [152][153][154][155]. A number of Phase I/II immunization trials have been conducted so far using P53 immunogens, but unfortunately none of them have shown acceptable clinical efficacy [156].…”
Section: Targeting Tp53 In Drug Developmentmentioning
confidence: 99%
“…Of the 19 patients treated, 1 showed complete regression (5%), 11 demonstrated partial regression (58%), 3 showed stable disease (16%), 2 showed progressive disease (11%), and 2 were unevaluable (11%). In a bladder carcinoma trial, 12 patients received either intratumoral or intravesicular injections of rAd-p53 at doses of 7.5 ϫ 10 11 to 7.5 ϫ 10 13 VP (Kuball et al, 2002). Higher transduction efficiency was observed when using the intravesicular delivery method.…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of adenovirus carrying p53 with a transduction enhancing agent improved p53 gene delivery and protein expression was found in patient tissue samples (Kuball et al 2002). Though higher doses of the virus were administered, no dose toxicity was observed (Kuball et al 2002). Similarly no serious adverse effects were reported by Malmstrom et al from a recently concluded Phase I/IIa trial using AdCD40L (Malmstrom et al 2010).…”
Section: Gene Therapy Clinical Trialsmentioning
confidence: 96%
“…However, adenovirus therapy was safe and well tolerated (Pagliaro et al 2003). Delivery of adenovirus carrying p53 with a transduction enhancing agent improved p53 gene delivery and protein expression was found in patient tissue samples (Kuball et al 2002). Though higher doses of the virus were administered, no dose toxicity was observed (Kuball et al 2002).…”
Section: Gene Therapy Clinical Trialsmentioning
confidence: 99%